A Whole-Cell Screen for Adjunctive and Direct Antimicrobials Active against Carbapenem-Resistant Enterobacteriaceae. (September 2019) - Smith, Kenneth P.; Dowgiallo, Matthew G.; Chiaraviglio, Lucius; Parvatkar, Prakash; Kim, Chungsik; Manetsch, Roman; Kirby, James E.
Carbapenem-resistant Enterobacteriaceae (CRE) are an emerging antimicrobial resistance threat for which few if any therapeutic options remain. Identification of new agents that either inhibit CRE or restore activity of existing antimicrobials is highly desirable. Therefore, a high-throughput screen of 182, 427 commercially available compounds was used to identify small molecules which either enhanced activity of meropenem against a carbapenem-resistant Klebsiella pneumoniae ST258 screening strain and/or directly inhibited its growth. The primary screening methodology was a whole-cell screen/counterscreen combination assay that tested for reduction of microbial growth in the presence or absence of meropenem, respectively. Screening hits demonstrating eukaryotic cell toxicity based on an orthogonal screening effort or identified as pan-assay interference compounds (PAINS) by computational methods were triaged. Primary screening hits were then clustered and ranked according to favorable physicochemical properties. Among remaining hits, we found 10 compounds that enhanced activity of carbapenems against a subset of CRE. Direct antimicrobials that passed toxicity and PAINS filters were not, however, identified in this relatively large screening effort. It was previously shown that the same screening strategy was productive for identifying candidates for further development when screening known bioactive libraries inclusive of natural products. Our findings therefore further highlight liabilities of commercially available small-molecule screening libraries in the Gram-negative antimicrobial space. In particular, there was especially low yield in identifying compelling activity against a representative, highly multidrug-resistant, carbapenemase-producing K. pneumoniae strain.